Diplomatic games : sport, statecraft, and international relations since 1945 - Dichter, Heather; Johns, Andrew L., 1968- (Studies in conflict, diplomacy, and peace., 2014)
"In Diplomatic Games, a team of international scholars examines how the nexus of sport and foreign relations has driven political and cultural change since 1945, demonstrating that governments have used athletic competition to maintain and strengthen alliances, promote politics, and increase national prestige. The contributors investigate topics such as China's use of sports to opposed Western imperialism, the ways in which sports helped bring an end to apartheid in South Africa, and the impact of the United States' 1980 Olympic boycott on U.S.-Soviet relations. Bringing together innovative scholarship from around the globe, this groundbreaking collection makes a compelling case for the utility of sport as a lens through which to view international relations."--Back cover.